Teeth loss and its association with locomotive syndrome among patients visiting the outpatient department of a dental school in Mahbubnagar, India-A cross sectional study: Teeth loss and its association with locomotive syndrome among patients of a dental school in Mahbubnagar, India-A cross sectional study - Nagilla, Jithender; Nagarajan, Sripriya; Trovagunta, Lakshmi Gyathri; Gakkula, Harish; Anuup, Kumaar P; Rampalli, Viswa Chandra (Acta Biomedica Atenei Parmensis, 2021)
BACKGROUND: Locomotive syndrome (LoS) is condition wherein mobility functions such as sit-to-stand or gait are declined due to locomotive organ impairment. The important risk factors for the LoS are ageing and physical factors. Physical factors significantly associated with dental statusAim: To investigate the relationships between teeth lost and locomotive syndrome.Materials and method: A cross sectional study was carried among (45-90 years) individuals by using Loco Check List. Factors related to demographics (age, sex) and number of teeth lost were assessed. Pearson’s chi-square test, multiple logistic regression analysis were performed. p 60 years age group. Majority of the subjects with tooth loss more than 10 teeth (92.6%) had a locomotive syndrome followed by the subjects with tooth loss 1-10 teeth (52.1%). Multiple logistic regression analysis revealed Locomotive syndrome was significantly (P= 0.000) higher among older age groups (>60 years) when compared with the 45- 60 years age group (or = 0.732) and subject with more than 10 teeth lost when compared with others (or = .009,or = 0.105)Conclusion: Study indicates that older age and number of teeth lost affect the prevalence of locomotive syndrome. Hence, maintaining oral health is necessary to retain more number of teeth throughout life which reduces the risk of locomotive syndrome.